2020
DOI: 10.21203/rs.3.rs-28873/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Difficulties doctors experience during life-sustaining treatment discussion after enactment of the Life-Sustaining Treatment Decisions Act: A cross-sectional study

Abstract: Background In the Republic of Korea, life-sustaining treatment (LST) for patients at the end of life should be legally discussed by a doctor according to the LST Decisions Act, which was enacted in February 2018. However, little is known about challenges doctors experience during LST discussion. This study aims to investigate the perceived difficulties of doctors during LST discussions after enactment of the new Act. Methods A cross-sectional survey was conducted in a tertiary hospital in August 2019 and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…For various reasons, physicians and parents may have different views about the process and the outcomes of the decision-making. This result from our review was consistent with the results of four quantitative studies that identified a barrier of discrepancies between physicians and parents [80][81][82][83]. In their studies, most paediatricians considered disagreements between physicians and parents about a child's diagnosis and prognosis in the medical assessment to be an important issue in the decision-making process [80][81][82][83].…”
Section: Involvement Of Parents In the Decision-making Processsupporting
confidence: 89%
“…For various reasons, physicians and parents may have different views about the process and the outcomes of the decision-making. This result from our review was consistent with the results of four quantitative studies that identified a barrier of discrepancies between physicians and parents [80][81][82][83]. In their studies, most paediatricians considered disagreements between physicians and parents about a child's diagnosis and prognosis in the medical assessment to be an important issue in the decision-making process [80][81][82][83].…”
Section: Involvement Of Parents In the Decision-making Processsupporting
confidence: 89%
“…Presently, the legal transactional mode of advance planning is shifting toward a communication model that accurately translates the patient's wishes [23]. A recent study found that many doctors in SNUH had serious difficulties communicating with patients and family members during LST discussions [24].…”
Section: Discussionmentioning
confidence: 99%
“…LST is de ned as any treatment that serves to prolong life without reversing the underlying medical condition and includes processes such as mechanical ventilation, renal dialysis, chemotherapy, antibiotics, and arti cial nutrition and hydration [7,8]. The relevant Acts aim to protect the best interests of the patients and respect their self-determinants rights [9]. In countries where well-dying related legislation was implemented earlier, there have been numerous studies and interventions on LST.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' perceptions of end-of-life care [10,11], as well as related physicians' orders [12,13], and ethical considerations [14,15] were discussed. However, in Korea, not long after the Well-dying Act was enacted, social consensus is still in the process of developing, so there are not many preceding studies examining the perceptions of seriously ill patients and the elderly toward preparation for death or receiving LST [1,9]. Therefore, this study aimed to investigate factors affecting decision making about LST among the Korean elderly and, in particular, examine the association between perceived life satisfaction and attitudes toward LST.…”
Section: Introductionmentioning
confidence: 99%